Association of CACNA1C and SYNE1 in offspring of patients with psychiatric disorders. (30th November 2016) - Gassó, Patricia; Sánchez-Gistau, Vanessa; Mas, Sergi; Sugranyes, Gisela; Rodríguez, Natalia; Boloc, Daniel; de la Serna, Elena; Romero, Soledad; Moreno, Dolores; Moreno, Carmen; Díaz-Caneja, Covadonga M.; Lafuente, Amalia; et al.
Abstract: Schizophrenia (SZ) and bipolar disorder (BD) are severe mental diseases associated with cognitive impairment, mood disturbance, and psychosis. Both disorders are highly heritable and share a common genetic background. The present study assesses, for the first time, differences in genotype frequencies of polymorphisms located in genes involved in neurodevelopment and synaptic plasticity between genetic high-risk individuals (offspring of patients with SZ or BD; N=100: 31 and 69, respectively) and control subjects (offspring of community controls; N=96). Individuals from both groups had similar ages, around 12 years. A higher percentage of men were included in the genetic high-risk group (58%) compared with the control group (40.6%). A total of 244 validated SNPs located in 35 candidate gene regions were analyzed in 196 participants. Multivariate methods based on logistic regression analysis were performed to assess differences in genotype frequencies. Bonferroni correction was applied for the multiple comparisons performed. Two polymorphisms, CACNA1C rs10848683 and SYNE1 rs214950, showed significant differences. The frequency of heterozygotes for CACNA1C rs10848683 in genetic high-risk individuals was double that in controls (OR=3.15; P=0.00016). For SYNE1 rs214950, higher frequencies of heterozygotes (OR=1.97) and homozygotes for the minor allele (OR=17.89; P=0.00020) were found in the genetic high-risk group than in the control group. In conclusion, polymorphisms in CACNA1C and SYNE1 could confer a greater risk of developing SZ and BD in individuals who are already at high risk because of their family history. This could help identify subjects with a very high genetic risk, in whom early detection and early intervention could lead to better prognosis. Highlights: Genetic association study in high-risk SZ or BD individuals (offspring of patients). A total of 35 genes involved in neurodevelopment and synaptic plasticity were assessed. Significant differences in genotype frequencies of CACNA1C and SYNE1 SNPs between controls and high-risk subjects were detected.